ANALISIS PENDAPATAN PETANI JAGUNG HIBRIDA DAN PADI TADAH HUJAN DI BUNGA MAYANG OKU TIMUR - Saiful Bahrie (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2015)
The purpose of this research were to : (1) To determine the average size of the production costs incurred by the farmer example hybrid maize and rainfed rice, (2) To determine the average amount of revenue and income earned by farmers examples of hybrid maize and rainfed rice, (3) To know the advantages of hybrid corn farming and rainfed rice farming. This research has been conducted in the district of East OKU District Bunga Mayang, Determining location with intentionally (purposive) on the basis that in the District Bunga Mayang East Oku District is an area of cultivation of hybrid maize and rainfed rice. This research was conducted in May and June 2013. The study found that the average cost of production in the farming of hybrid corn in one production process is Rp. 10,672,672.73 / ha / mt danusahatani rainfed rice in one production process is Rp9.680.480 ha / mt. Average production in the farming of hybrid corn in one process produksiadalah 7,84 ton / ha / mt of maize pipil keringdan rainfed rice farming in one production process is 2.641kg / ha / mt rice. The average cost of cultivation of hybrid corn in the production process is higher than rainfed rice farming. Farmers' income to farming corn hybrids in one production process is higher than rainfed rice farming is Rp11.524.250 / ha / mt corn dry pipil and Rp. 8.161.597ha / mt rice. At the level of the test using the t-test obtained t 9.530> 0.683 ttabel which means that Ho refused and Ha accepted.